2014
DOI: 10.1063/1.4867492
|View full text |Cite
|
Sign up to set email alerts
|

A plasma source driven predator-prey like mechanism as a potential cause of spiraling intermittencies in linear plasma devices

Abstract: Three-dimensional global drift fluid simulations are carried out to analyze coherent plasma structures appearing in the NAGDIS-II linear device (nagoya divertor plasma Simulator-II). The numerical simulations reproduce several features of the intermittent spiraling structures observed, for instance, statistical properties, rotation frequency, and the frequency of plasma expulsion. The detailed inspection of the three-dimensional plasma dynamics allows to identify the key mechanism behind the formation of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
(42 reference statements)
5
16
0
Order By: Relevance
“…Reiser et al discussed based on three-dimensional global drift fluid dynamics simulation that spiral structures, like the one observed in the NAGDIS-II device, is dominated by m = 1 and m = 2 modes with a time oscillation of m = 0 mode [12]. Thus, the present mode analysis are qualitatively agree well with the global drift fluid dynamic simulation.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Reiser et al discussed based on three-dimensional global drift fluid dynamics simulation that spiral structures, like the one observed in the NAGDIS-II device, is dominated by m = 1 and m = 2 modes with a time oscillation of m = 0 mode [12]. Thus, the present mode analysis are qualitatively agree well with the global drift fluid dynamic simulation.…”
Section: Resultssupporting
confidence: 80%
“…In this study, the characteristic time scale of the phenomena was in the range of 10 -20 kHz. Tanaka et al showed under a different condition in NAGDIS-II that the ejection frequency was approximately 3.2 kHz [10], and it was 2.0 kHz in simulation [12]. Although the rotation frequency of blob-like plasma has been revealed to depend on the magnetic field strength and density profile, no detailed investigation has yet to be conducted for the ejection frequency; the results in this study suggested that the ejection frequency also altered by the plasma condition.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…When the ion flux dramatically decreases due to an increase of the neutral gas pressure, a large amplitude ion flux fluctuation with ≤ 10 kHz components was detected by using a circular end-target plate with a diameter of 50 mm [4]. Threedimensional simulation suggested that such axisymmetricmode fluctuation generates intermittent plasma structures in the periphery [5], however, there were a few measurements of this fluctuation. In addition, it is not known where the large amplitude fluctuation occurs in the detached plasma.…”
mentioning
confidence: 99%